Mirror – Landscape – Swedenborg. On the Secret of Reflections in Selected Poems by Leopold Staff - Borek, Bartłomiej (Hybris, 2025)
The article analyzes selected works of Leopold Staff through the lens of Emanuel Swedenborg’s philosophy, focusing on the motif of mirror reflections as a cognitive medium. The mirror – both literal and metaphorical – serves in Staff’s poetry as a symbol of transition between the sacred and the profane and as an epistemological tool for revealing the boundaries of human perception. The author highlights Swedenborg’s role as a key interpreter of these relations, drawing analogies between his vision of reality and Staff’s poetic imagery. The analysis also considers concepts such as synesthesia, correspondence, and sacrofanalization, offering a novel research perspective.